The Impact of Economic Development on the Reproduction of Rural Elites: Field Study in M’ziraa Municipality, Biskra City-Algeria- - Mokhnane, Tarek (جامعة محمد خيضر بسكرة, 2023)
Through this empirical study, which is interested in the modes of action and intervention of social groups operating in the municipality of M'Ziràa, likely to have an effect on territorial development, we attempt to characterize the local rural elites. , retrace their history and process of evolution, estimate their symbolic capital as well as their role in local development. It also aims to understand the mechanisms of production and reproduction of this social category.
Keywords: النخب الريفية -- التنمية الاقتصادية -- التنمية الإقليمية -- الجزائر